PELATIHAN BAHASA INGGRIS PEMANDU WISATA LOKAL DI DESA KAPAL - I. N. Sudipa; I. M. Rajeg; L. P. Laksminy (Buletin Udayana Mengabdi, 2014)
The training of Practical English for local guides was conducted in Kapal-Mengwi. The materials focused on the language functions, among others: Greeting, Apologizing and Requesting. Through the methods: orientation, drills, feedback and continuation, the participants-Pokdarwis members managed to use them practically. The only obstacle they might face is the pronunciation of [th].Keywords: Pokdarwis, pronunciation